Evaluation of the Potential Prognostic Value of Tumor Budding in Laryngeal Carcinoma by Conventional and Immunohistochemical Staining. (16th November 2020) - Abd Raboh, Nermine M.; Mady, Ossama M.; Hakim, Sarah A.
Abstract : Background . Tumor budding is a promising prognostic indicator in several cancers especially in colorectal cancer. However, only few studies have been conducted to assess and validate its prognostic value in laryngeal squamous cell carcinoma; none of which used pancytokeratin immunohistochemistry. In view of the modest results of treatment of laryngeal squamous cell carcinoma, the need of new prognostic indicators becomes of paramount importance. Aim of the Study . We aim to evaluate tumor budding in laryngeal squamous cell carcinoma, by haematoxylin and eosin, as well as by pancytokeratin immunohistochemistry. Material and Methods . A retrospective study on 118 cases of laryngeal squamous cell carcinoma from archives of Pathology Lab of Ain Shams University Specialized Hospital and Ain Shams University Hospitals from January 2014 to January 2017. The ENT and histopathology reports were reviewed to determine clinicopathologic data of the patients. Results . Tumor budding shows high statistically significant relations (p = 0.0001 for each) with important clinicopathological parameters of laryngeal carcinoma (site, grade, tumor stage, lymph node stage, lymph node extracapsular invasion, and vascular invasion). The extent of tumor budding correlated with overall survival, local recurrence disease free, and distant metastasis disease free (p = 0.001 for each). Multivariate analysis showed tumor budding to be an independent prognostic factor affecting progression-free survival. There was a moderate agreement between H&E and IHC by pancytokeratin as regards detection of budding among study cases (kappa = 0.593 ). Conclusions . Tumor budding was correlated with poor prognostic clinicopathologic indicators in laryngeal squamous cell carcinoma. It is recommended to use pancytokeratin immunohistochemistry to evaluate tumor budding in laryngeal squamous cell carcinoma especially in confusing cases.